Fluorescent Live‐Cell Imaging of Metabolically Incorporated Unnatural Cyclopropene‐Mannosamine Derivatives. Issue 2 (4th January 2013) - Cole, Christian M.; Yang, Jun; Šečkutė, Jolita; Devaraj, Neal K.
<x xml:space="preserve">Abstract</x> Sugar coated: We recently developed methylcyclopropenes as low‐molecular‐weight tetrazine coupling partners. Here, we demonstrate that methylcyclopropenes can meet the stringent steric demands required for metabolic imaging of unnatural mannosamines on live cells. Using sequential azide–alkyne chemistry, we also demonstrate multicolor imaging of two different metabolically incorporated unnatural sugars.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>